Hydrological Characteristics of Groundwater in the East Baghdad Oil Field (Rashidiya and the Southern Region Using GIS) - Kazem, Azraa Lafta; Al Ibrahimi, Suhaila Najem (Journal of Ecohumanism, 2025)
After knowing the natural phenomena, we will study in this chapter the characteristics of groundwater through spatial analysis of wells and their geographical distribution, renewing the depths of wells, the direction and movement of groundwater, well recharge, determining their fixed and variable levels, and chemical and physical characteristics. The study was based on a sample of (40) wells distributed in a different way in the region. The spatial analysis of groundwater is done by estimating and measuring the value of groundwater, which has a fundamental role in water management, as it gives a clear idea about the volume of groundwater, its production capacity, its level, and the number of wells and their depths in the region